Introductory Note to the Special Issue: Teaching as an Intergenerational Profession: How Generational Diversity Contributes to Teacher Education and Professional Development (Revista Lusófona de Educação, 2026)
Introdución al dossier tematico:La docencia como profesión intergeneracional: cómo la diversidad generacional contribuye a la formación y el desarrollo profesional del profesorado.